The politics of acknowledgement : truth commissions in Uganda and Haiti - Quinn, Joanna R. (Law and society series (Vancouver, B.C.), 2010)
<!DOCTYPE html PUBLIC "-//W3C//DTD HTML 3.2//EN"> Human rights violations leave deep scars on people, societies, and nations. Rights groups argue that resolving past violence is necessary for a peaceful future. But how can nations ensure that instruments of transitional justice are the best path to reconciliation? This book develops a theoretical framework - a framework of acknowledgement - to evaluate truth commissions. Analysis of the difficulties encountered and the ultimate failure of truth commissions in Uganda and Haiti reveals that acknowledgement of past violence - by both victims and perpetrators - must come before goals such as forgiveness and social cohesion if reconciliation is to be achieved.